2010
DOI: 10.1108/02683941011089134
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence correlates of the four‐factor model of cultural intelligence

Abstract: Purpose -The purpose of this research is to examine relationships between emotional intelligence and the four factor model of cultural intelligence -metacognitive CQ, cognitive CQ, motivational CQ, and behavioral CQ. Design/methodology/approach -Confirmatory factor analyses and hierarchical regression analyses on data from 381 students in Korea are conducted. Findings -The results support discriminant validity of the four factor model of cultural intelligence scale (CQS) in relation to the emotional intelligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
6

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 30 publications
10
123
0
6
Order By: Relevance
“…The authors concluded that if expatriates have higher Emotional Intelligence scores, then the probability of them being successful in a foreign assignment is very high. Similarly, in a study involving Korean students, Moon (2010) found that Cultural Intelligence (CQ) positively correlated with self-competence (self-awareness and relationship management). So, this study reinforces the point that one of the major contributors of success in a foreign assignment is self-competence of an expatriate.…”
Section: Culture Shock and Expatriatesmentioning
confidence: 99%
“…The authors concluded that if expatriates have higher Emotional Intelligence scores, then the probability of them being successful in a foreign assignment is very high. Similarly, in a study involving Korean students, Moon (2010) found that Cultural Intelligence (CQ) positively correlated with self-competence (self-awareness and relationship management). So, this study reinforces the point that one of the major contributors of success in a foreign assignment is self-competence of an expatriate.…”
Section: Culture Shock and Expatriatesmentioning
confidence: 99%
“…A number of studies (e.g., Crowne, 2009Crowne, , 2013Moon, 2010) have examined the relationship between emotional intelligence and cultural intelligence showing that the two concepts may be related but still distinct concepts. Therefore, emotional intelligence may be influenced by the cultural background of the individual and lead to different conflict handling styles.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Aspects of CQ include meta-cognitive CQ, cognitive CQ, motivational CQ, and behavioral CQ. The researcher has employed the measure developed by Moon, 2010) to measure CQ. It is worthy of mention that this measure consists of the 20 items.…”
Section: Research Variables and Methods Of Measuring 431 Cultural Imentioning
confidence: 99%
“…It assesses four items for meta-cognitive CQ, six for cognitive CQ, five for motivational CQ and five for behavioral CQ. It is a self rating scale consisting of 20 items; taking this test means giving oneself a mark from 1 (disagree) to 5 (strongly agree) on each of the items , 2010Moon, 2010). Those with high levels of CQ are much more successful when interacting with people from different cultures.…”
Section: The Measurement Of Cqmentioning
confidence: 99%